Spectrum of clinical research in juvenile idiopathic arthritis: a cross-sectional analysis of registered studies in clinicaltrials.gov and clinicaltrialsregister.eu - Lehmann, Ronny; Ries, Markus (Biomedicines, 2021)
The management of juvenile idiopathic arthritis (JIA) has improved tremendously in recent years due to the introduction of new drug therapies but remains complex in terms of non-pharmaceutical issues. In order to determine the direction of scientific progress by characterizing the current spectrum of ongoing clinical research in JIA, we analyzed all ongoing studies in the field of JIA—registered in clinicaltrials.gov and clinicaltrialsregister.eu—concerning sponsoring, enrollment, duration, localization, and particularly objectives. The close of the database was 7 January 2021. After identifying double-registered studies, n = 72 went into further analysis. Of these, 61.1% were academia-sponsored and 37.5% were sponsored by the pharma industry. The majority of the studies was of the interventional type (77.8%), while others (22.2%) were observational. The median planned enrollments were 100 participants (interventional studies) and 175 participants (observational studies), respectively. The duration differed remarkably from one month to more than 15 years, with a median of 42.5 months. A total of 61.1% of studies were located in a single country, and 38.9% were in several. Europe and North America clearly dominated the study localizations. The study objectives were DMARDs (56.9%), followed by diagnostics and disease activity measurement (18.1%), and medication other than DMARD (12.5%), besides others. Studies on DMARDs were mainly sponsored by industry, predominantly interventional studies on established and novel biologics, with several on specific issues such as systemic JIA and others. The spectrum of registered studies is currently centered on drug therapy and diagnostics, while other issues in JIA play a subordinated role in current research. Drug development was transferred from adult rheumatology into the JIA population with little innovation for children. Future research should take specific pediatric needs better into account.
Gesehen am 26.01.2022